Bio-based Acacia catechu/Ferric Oxide Nanostructured Composite Electrodes for Advanced Energy Storage Materials (Patan Pragya, 2024)
This study explores the bio-based nanocomposite electrodes for advanced energy storage, combining nanostructured ferric oxide (Fe₂O₃) with highly porous activated carbon (PAC) derived from Acacia catechu wood waste. Instrumental analysis confirmed the PAC's desirable structural characteristics, including high surface area and porosity, suitable for electrochemical applications. Initial evaluation of the PAC electrode revealed a specific capacitance of 57.4 Fg⁻¹ at 1 Ag⁻ ¹, 79.1% ca pacitance retention after 1000 cycles, and an energy density of 4.8 Wh kg⁻¹ at a power density of 159.1 W kg⁻ ¹. Significantly, compositing PAC with Fe₂O₃ at a 1:1 ratio dramatically enhanced electrochemical performance. The resulting 1:1 (PAC:Fe) nanocomposite exhibited a superior specific capacitance of 104.3 F g⁻¹ at 1 Ag⁻ ¹, a remarkable 96.3% capacitance retention after 1000 cycles, and an elevated energy density of 8.3 Wh kg⁻¹ at a power density of 275.0 W kg⁻¹, achieved in a 6 M KOH electrolyte using a three-electrode setup with a 1.55 V working voltage.